Efeito do tratamento com o complexo paladaciclo DPPE 1.1 associado ao DPPE 1.2 sobre a infecção pela Leishmania (Leishmania) amazonensis in vitro e in vivo - Motta, Priscila Dias [UNIFESP] (2016)
The present study evaluated the efficacy of the treatment with the pallladacycle complex DPPE 1.1 associated to DPPE 1.2 on in vitro and in vivo Leishmania (Leishmania) amazonensis infection. The determination of the pharmacodynamic interaction of the two associated compounds in vitro was performed by use of DPPE 1.1 and DPPE 1.2 given alone or combined for the treatment of BALB/c bone marrow macrophages infected with L. (L.) amazonensis. In a first screening only one value of the fractional inhibitory concentration (FIC) of DPPE 1.1 and DPPE 1.2 was used and the data showed a synergistic effect between them. However, the fixed-ratio isobologram method leads to a higher reproducibility for drug interaction studies. So, the association between DPPE 1.1 and DPPE 1.2 was evaluated using this method and several FIC values were determined. The FICs were used for construction of a fixed-ratio isobologram which indicated an indifferent or additive interaction for DPPE 1.1 combined with DPPE 1.2. The in vivo treatment with DPPE 1.1, DPPE 1.2 or both associated was performed in L. (L.) amazonensis-infected BALB/c mice. In a first assay, the reduction of parasite load in animals treated with DPPE 1.1 associated with DPPE 1.2 was 50 fold higher than that estimated in mice treated with the same doses of DPPE 1.1 and DPPE 1.2 alone. Next, the ED50 was initially determined for each of the drugs given alone. Based on their ED50 values, different proportions of DPPE 1.1 associated with DPPE 1.2 were tested for determination of the ED50 of the drugs in combination whose values were used to calculate the activity enhancement index (AEI). The AEI indicated that DPPE 1.1 and DPPE 1.2 have possibly synergistic effect in vivo. The leishmanicidal activity in mice treated with DPPE 1.1 and DPPE 1.2 alone or associated was followed by a significant increase of T CD4+ lymphocytes. Treated mice also exhibited a small but not significant increase of T CD8+ lymphocytes. All treated mice displayed significantly lower levels of active TGF-? and higher of IFN-? compared to untreated controls, indicating a predominance of inflammatory responses in treated animals.